Pengembangan Model Pembelajaran Sejarah Wisata Negeri Dongeng Berbasis Taman Miniatur Melalui Pendekatan Outdoor Study di SMA Negeri Ponggok Blitar - Fandu Dyangga; Novi Catur Muspita (Universitas Islam Balitar, 2021)
History learning is one of the lessons that are required to be able to provide wisdom value and character education to students as a form of response to the challenges of the current development of globalization. In this study, the researchers tried to carry out a learning innovation by applying the development of a historical learning model based on the tourism object of the Fairy Tale Miniature Park in Ponggok Village, Blitar Regency. The purpose of this research; (1) Describe the condition of the History Learning in SMA Negeri Ponggok. (2) Developing a model of learning history based on the Fairy Tale Miniature Park with the Outdoor Study approach. (3) To test the effectiveness of the historical learning model based on the Fairy Tale Miniature Park with the Outdoor Study approach. This research is based on the criteria for research and development (R&D) with the ADDIE Model learning design. This research is divided into 3 stages of implementation, namely; the preliminary stage, the model development stage and the final stage of the effectiveness test. This research resulted in the textbook Monograph and HKI as an additional output and mandatory output to be published in a National Accredited Journal, namely Translitera. The results of this study can be seen that there are differences in learning outcomes between the Control class (XI IPS 1) and the Experiment class XI IPS 3) which can be seen from the results of the trials at each stage. Based on the results of the SPSS count statistical test, it can be concluded that the history learning model based on fairy tale tourism can be used to achieve student learning effectiveness.